Contextualising the global information revolution in a development arena: - A. Grossberg A. Grossberg; Jarè Struwig Jarè Struwig; Kholadi Tabela Tlabela (Communicare)
The focus of this article is to contextualise information communication technology (ICT) development within the global information arena through reference to a particular case study where an ICT was implemented in various areas in South Africa. The article sheds light on often-conflicting ideologies relating to the effect of information technology in developing countries in general and in South Africa in particular. It presents an overview of problems and possible solutions regarding acceptability, use, sustainability, and best practices. From a research perspective the article investigates how development initiatives can be supported by adapting this computerised system to the needs of users within specific contexts. It also intends to discuss general prohibiting factors in a development arena extending from implementation to usage at various levels involving diverse role players.